2016
DOI: 10.4103/0975-7406.199336
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of cost of illness for diabetic patients in South Indian tertiary care hospital

Abstract: Background:The impact of diabetes on health-care expenditures has been increasingly recognized. To formulate an effective health planning and resource allocation, it is important to determine economic burden.Objective:The objective of this study is to assess the cost of illness (COI) for diabetic inpatients with or without complications.Methodology:The study was conducted in the medicine wards of tertiary care hospital after ethical approval by the Institutional Ethical Committee. A total of 116 each diabetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 12 publications
4
18
0
Order By: Relevance
“…This finding was in concordance with the study done by Leelavathi D, et al, [20] (2017) on Assessment of cost of illness for diabetic patients in South Indian tertiary care hospital which stated that cost of illness is comparatively high in patients with complications than Diabetes alone Similarly literature stated that macrovascular comorbid conditions are a major driver of health care costs in patients with diabetes, including both increased direct health care cost and lost indirect productivity cost.…”
Section: Discussion:-supporting
confidence: 89%
“…This finding was in concordance with the study done by Leelavathi D, et al, [20] (2017) on Assessment of cost of illness for diabetic patients in South Indian tertiary care hospital which stated that cost of illness is comparatively high in patients with complications than Diabetes alone Similarly literature stated that macrovascular comorbid conditions are a major driver of health care costs in patients with diabetes, including both increased direct health care cost and lost indirect productivity cost.…”
Section: Discussion:-supporting
confidence: 89%
“…[5][6][7] It was observed that, though majority of the study participants were belonging to lower socio economic class (class 1 and 2 of BG Prasad's classification of socio economic stratification), only, one third of the participants were covered by one of the (33.18%) social security scheme for health insurance. Rest two thirds of the population was forced to spend out of pocket.…”
Section: Discussionmentioning
confidence: 94%
“…[27] Acharya et al assessed the costs of illness for diabetes patients with or without complications hospitalized in a tertiary care hospital; they concluded that diabetes patients with renal and cardiac complications incurred greater expenses than those with other chronic complications. [28] These studies only investigated the cost of concordant comorbidities and complications associated with diabetes. As our study has taken into account both concordant and discordant comorbidities, comparability to these studies is limited.…”
Section: Discussionmentioning
confidence: 99%